Hypoxic Stress Induces Transient Receptor Potential Melastatin 2 (TRPM2) Channel Expression in Adult Rat Cardiac Fibroblasts - Kenji Takahashi; Kazuho Sakamoto; Junko Kimura (Elsevier, 2012)
When cardiac tissue is exposed to hypoxia, myocytes are damaged, while fibroblasts are activated. However, it is unknown what changes are induced by hypoxia in cardiac fibroblasts. In this study, using the whole cell patch-clamp technique, we investigated the effect of hypoxia on membrane currents in fibroblasts primarily cultured from adult rat hearts. Cardiac fibroblasts were incubated for 24 h under normoxic or hypoxic conditions using Anaeropack. Hypoxia increased a current which reversed at around −20 mV in the cardiac fibroblasts. This current was inhibited by clotrimazole, which is an inhibitor of transient receptor potential melastatin 2 (TRPM2) channel and intermediate-conductance Ca2+-activated K+ channel (KCa3.1). ADP ribose in the pipette solution enhanced this current. Quantitative RT-PCR revealed that mRNA of TRPM2, but not that of KCa3.1, was increased by hypoxia. RNA interference of TRPM2 prevented the development of the hypoxia-induced current. H2O2, an activator of TRPM2 channel, induced a higher [Ca2+]i elevation in hypoxia-exposed cardiac fibroblasts than that in normoxia-exposed cells. We conclude that hypoxia induces TRPM2 channel expression in adult rat cardiac fibroblasts. Keywords:: hypoxia, cardiac fibroblast, rat heart, clotrimazole, transient receptor potential melastatin 2 (TRPM2) channel